2020
DOI: 10.1111/jpm.12611
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with internalized stigma for Indonesian individuals diagnosed with schizophrenia in a community setting

Abstract: Accessible summary What is known on the subject? Internalized stigma in people diagnosed with mental illness has several negative outcomes; however, it remains unclear in an Indonesian context. The human rights of people diagnosed with mental illness in Indonesia have been routinely violated because of the existing stigma against mental illness and deficiencies in the country's mental healthcare services. What the paper adds to existing knowledge? To the best of our knowledge, this is the first study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 46 publications
9
23
0
2
Order By: Relevance
“…This finding is in line with a study from China conducted among severe mental disorders in rural communities using the same tool for measuring stigma [25]. However, this estimate is higher compared to most other studies within Nepal [15,17] and other parts [8,28] of the world. Studies comparing stigma scores within diagnostic categories have persistently reported higher self-stigma scores for schizophrenia and psychosis compared to affective disorders and this could be the main reason behind the discrepancy reported [25,29].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with a study from China conducted among severe mental disorders in rural communities using the same tool for measuring stigma [25]. However, this estimate is higher compared to most other studies within Nepal [15,17] and other parts [8,28] of the world. Studies comparing stigma scores within diagnostic categories have persistently reported higher self-stigma scores for schizophrenia and psychosis compared to affective disorders and this could be the main reason behind the discrepancy reported [25,29].…”
Section: Plos Onesupporting
confidence: 89%
“…conducted elsewhere have reported inconsistent results with some studies reporting highest scores for alienation [14] and least for endorsement subscale [9,14,30], and other studies reporting highest scores for discrimination experience [28,30] with the same assessment tool.…”
Section: Plos Onementioning
confidence: 91%
“…The level of stigma attracts more and more attention, as it has become one of the most important indicators to measure the recovery of schizophrenia patients (23). Previous research showed that when patients with schizophrenia were stable, they could still feel disappointed, isolated and helpless (24). When they are faced with misfortune or setback, the individual's acceptance of their own shortcomings and understanding of their own abilities are defective.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review on mental health in Indonesia conducted in PubMed returned 161 studies published between 1949 and 2020. However, only 15 of these studies discussed stigma either directly or in the context of Indonesian mental health services [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Among these 15 studies, six discussed stigma in general, consequences of stigma (i.e., "pasung" or confinement), attitudes toward mental health, and perceptions of mental health [18,30,31,[41][42][43].…”
mentioning
confidence: 99%
“…However, only 15 of these studies discussed stigma either directly or in the context of Indonesian mental health services [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Among these 15 studies, six discussed stigma in general, consequences of stigma (i.e., "pasung" or confinement), attitudes toward mental health, and perceptions of mental health [18,30,31,[41][42][43]. Previous investigations of stigma in Indonesia mainly examined personal stigma, with a focus on the perceptions of those with mental illness and their families, how they respond to stigmatization in their lives, and the impact of stigma on access to mental health facilities or treatment [18,[20][21][22][23]44].…”
mentioning
confidence: 99%